The decidual expression of Interleukin‐7 is upregulated in early pregnancy loss. (29th May 2021) - Vilsmaier, Theresa; Amann, Niklas; Löb, Sanja; Schmoeckel, Elisa; Kuhn, Christina; Zati zehni, Alaleh; Meister, Sarah; Beyer, Susanne; Kolben, Theresa M.; Becker, Johanna; Mumm, Jan‐Niclas; Mahner, Sven; et al.
Abstract: Background: Maternal immunological rejection of the semi‐allogenic fetus is discussed as one of the significant factors involved in early pregnancy loss. An array of cytokines secreted by both maternal and fetal cells is involved in generating a delicate maternal immune tolerance. Interleukin‐7 (IL‐7) is discussed to play a key role in pro‐inflammatory processes, but there is still limited insight into the pathophysiological input on placentation and embryonic development in early pregnancy loss. Patients and methods: Cytokine level differences were identified with quantitative real‐time PCR in placental tissue from spontaneous abortions (SA) ( n = 18), recurrent spontaneous abortions (RSA) ( n = 15), and healthy pregnancies ( n = 15) at gestational weeks 7 to 14. Protein expression of IL‐7 in the decidua was investigated by immunohistochemistry. IL‐7‐expressing cells were identified with double‐immunofluorescence. Results: Decidua of women with RSA expressed almost 51‐times higher values of IL‐7 in gene expression analysis. Immunohistochemistry identified a significant upregulation of IL‐7 in the decidua of RSA specimens ( p = .013) and in the decidua of women with SA ( p = .004). Double‐immunofluorescence confirmed decidual stroma cells as IL‐7‐expressing cells. Conclusion: Significantly elevated IL‐7 values in the decidua of spontaneous and recurrent miscarriages imply a crucial role of the cytokine in the signaling at the feto‐maternal interface of the placenta. An overexpression of IL‐7 could result in early pregnancy loss by inducing a pro‐inflammatory environment. Proven to be valuable in other autoimmune diseases, targeting IL‐7 signaling therapeutically may prove to be a very beneficial treatment option for RSA patients.